Instilling Character Education Through Habituation at School with the Help of Parents - Sutrisno Sutrisno; Isrohmawati Isrohmawati; Emi Bahrul Munif; Jemmy Jemmy; Abdul Wahab (Yayasan Adra Karima Hubbi, 2023)
Background. Islamic education is a process to provide and gain knowledge that occurs between students and educators to carry out the learning process in an Islamic perspective, explained how the concept of instilling character education through habituation in schools with the help of parents. It can be seen that the character of today's students has not developed well. Here the role of educators and parents is to apply good habituation so that it has a good impact on students. Purpose. From This study aims to determine the character and habituation of a student and improve the student to have good morals. Method. This research uses quantitative methods with field survey models. Then researchers also conducted in-depth interviews with teachers and students directly. Results The results of this study explain that the role of instilling student character education through habituation in schools with the help of parents is very important in today's education. Conclusion. Conclusion There are many models of habituation models in effective and creative ways to improve the character of a student. The limitations of this study researchers have not found many ways to instill good character so that it is quickly accepted by students, researchers hope that the next researcher can instill good character and easily accepted by students, so that students can improve maximum learning outcomes.